1992
DOI: 10.1002/ana.410320716
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in levels of iron, ferritin, and other trace metals in neurodegenerative diseases affecting the basal ganglia

Abstract: Previously we have shown that cell death in the substantia nigra (SN) in Parkinson's disease (PD) is associated with an increase in iron content but a decrease in the level of the iron-binding protein ferritin. Alterations in other metal ion levels were also observed; copper levels were reduced, whereas zinc levels were increased. The importance of these changes in iron, ferritin, and other metal ions in the pathophysiology of PD depends on whether they are specific to the illness. We measured levels of iron, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(135 citation statements)
references
References 22 publications
(4 reference statements)
6
129
0
Order By: Relevance
“…Brain iron accumulation in association with neurologic symptoms has been observed in Hallervorden-Spatz disease, but the mechanisms of iron accumulation in the basal ganglia of these patients and the relationship of this to clinical symptoms is unknown (46). A direct role for iron-mediated tissue injury in the brain is supported by studies on the role of this metal in oxidant-mediated ischemia-reperfusion injury after stroke and cerebral hemorrhage and by data which demonstrate marked abnormalities in iron metabolism in a number of neurodegenerative disorders (47). In this regard, previous studies have revealed age-related decreases in human ceruloplasmin oxidase activity in the plasma, making it reasonable to speculate that such changes in the brain, in association with other environmental or genetic factors, may contribute to neurodegeneration observed with aging (48).…”
Section: Discussionmentioning
confidence: 99%
“…Brain iron accumulation in association with neurologic symptoms has been observed in Hallervorden-Spatz disease, but the mechanisms of iron accumulation in the basal ganglia of these patients and the relationship of this to clinical symptoms is unknown (46). A direct role for iron-mediated tissue injury in the brain is supported by studies on the role of this metal in oxidant-mediated ischemia-reperfusion injury after stroke and cerebral hemorrhage and by data which demonstrate marked abnormalities in iron metabolism in a number of neurodegenerative disorders (47). In this regard, previous studies have revealed age-related decreases in human ceruloplasmin oxidase activity in the plasma, making it reasonable to speculate that such changes in the brain, in association with other environmental or genetic factors, may contribute to neurodegeneration observed with aging (48).…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin is the major iron storage protein in the body which maintains iron in a nonreactive form in the cell. Results from several studies suggest that ferritin in the SNpc is not increased concomitantly with iron (26). Although it has been previously speculated that increasing iron loading by ferritin may increase the risk of free radical damage to the cell (27), a recent in vivo study has shown that genetically enhanced expression of ferritin and pharmacological iron chelation (clioquinol) prevents MPTP-induced neurotoxicity (28).…”
Section: Role Of Iron In Pd Pathogenesismentioning
confidence: 99%
“…In human nigral neurons the level of H-Frt is relatively low [2,26], and in PD the Frt level remained unchanged in the SN where the total iron level is increased [45]. H-Frt is degraded via both UPS and the autophagy-lysosome pathway [44,46].…”
Section: Discussionmentioning
confidence: 99%